Pengaruh Biaya Overhead Pabrik dan Biaya Tenaga Kerja Langsung terhadap Hasil Penjualan Pada Usaha Loyang Pak May Padang - Oktaviani, Nichy; Mardianto, Dedi; Handayani, Deby (SAFE-Network, 2023)
This study aims to determine the effect of factory overhead costs and direct labor costs on sales results in Pak May Padang's baking pan business. Taking this title is based on the phenomenon that many business actors do not understand the calculation of production reports so that sales results are not clear, as we can see for ourselves business actors often neglect recording financial reports, the need to know sales results so that they can determine the number of products to be produced and sold in more detail. This study uses a type of quantitative research. The data taken is in the form of secondary data by conducting direct interviews with business owners, by preparing question materials and looking at records of factory overhead costs and direct labor costs during the period 2018 to 2022. This study conducted a classic assumption test, hypothesis testing using SPSS version 21. With the results of the study stating Seeing the results of the tests that have been carried out proves that partially Factory Overhead Costs have a significant effect on Sales Results, direct labor costs have no significant effect on sales results and simultaneously both variables have a significant effect on Sales Results, and can also be seen Adjusted R Square of 0.501 or 50.1% This means that 50.1% of the Sales Results variable is influenced by Factory Overhead Costs and Direct Labor Costs, the remaining 49.9% is influenced by other variables outside of this research variable.